Relationship between Mothers Birth Spacing and Incidence of Stunting in Children 24 - 59 months - Ricko Eliafiana; Tubagus Ferdi Fadilah (Fakultas Kedokteran Universitas Trisakti, 2022)
Abstract: (1) Background: Stunting is one of the nutritional problems that occur in children under five years old. Based on maternal factors, the cause of stunting is a short birth spacing which results in a lack of energy recovery after giving birth to a previous child. This study aims to determine the relationship between birth spacing and stunting in children 24-59 months. (2) Methods: A cross-sectional observational study was conducted with a total of 130 children who with their parents attended monthly visits to the Public Health Center of Grogol Petamburan District West Jakarta, Indonesia in September-November 2019. Data were collected using z scores and questionnaires. The Chi-square test was performed for data analysis. (3) Results: The prevalence of stunting in this study was lower than the national prevalence and the incidence of stunting was higher in birth spacing below 2 years. Short interval birth spacing increases the risk of stunting. However, the relationship between childbirth spacing and incidence of stunting in children 24-59 months was not statistically significant. (4) Conclusions: Short interval of birth spacing is not a direct cause of stunting as there are other related modifiable factors.